Adopting Promising Agricultural Technologies: The Role of Policies and Trade - Gruère, Guillaume P. (2014)
"Adopting Promising Agricultural Technologies: The Role of Policies and Trade" by Guillaume Gruere, Trade and Agriculture Directorate Organisation for Economic Co-operation and Development. Presented at the Food Security in a World of Growing Natural Resource Scarcity event hosted by IFPRI on February 12, 2014 at the Newseum.